Valorisation of Camellia sinensis branches as a raw product with green technology extraction methods - V. Sanz; N. Flórez-Fernández; H. Domínguez; M.D. Torres (Current Research in Food Science, 2020)
This work deals with the study of tea stalks from pruning debris using environmental friendly extraction technology to offer new healthy properties. In the manufacturing tea industry, tea trees require to be pruned every year and most of their remains are discarded as a waste with no economic value. Microwave aqueous extraction and pressurized hot water extraction process (autohydrolysis) were used to recover bioactive compounds from the tea branches. Operating at a fixed solid: liquid ratio (1:15), the effect of the maximum heating temperatures from 140 to 220 °C was studied. Liquid extracts were analysed for total phenolic, oligosaccharides, protein, mineral and heavy metals content, as well as for antioxidant capacity. The antitumoral possibilities were also determined for selected samples. The obtained results indicated that both processes could be used as an alternative to recover bioactive compounds from tea wastes, although microwave-assisted extraction allowed saving time when compared with autohydrolysis processing. The temperature exhibited a relevant effect on the total phenolic content and antioxidant capacity, decreasing with the microwave treatment and increasing with the autohydrolysis temperature. The obtained extracts could be adequate for incorporation in food and non-food fields.